2010
DOI: 10.1097/scs.0b013e3181d87a42
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Bone Ratio of Mandible Using Micro-Computed Tomography in Korean

Abstract: Cortical bone and trabecular portion play important roles in maintaining the general structure of bone. It has been reported that a decrease in bone mineral density is related with increasing age, sex, and teeth loss. However, most of the studies were done with conventional radiographic analysis. In addition, data from Korean population are rare. The aim of this study was to analyze trabecular pattern of the mandible using micro-computed tomography. Thirty-nine specimens of the mandible were prepared. Specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Bone loss commences at the age of about 35 years, and continues at diVerent rates throughout life [6]. In the present study, the TBR did not diVer between the dentate and the edentulous subjects, although an age-related decrease in the TBR has been reported [23]. Age-related changes of mandible were well explained in previous studies.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Bone loss commences at the age of about 35 years, and continues at diVerent rates throughout life [6]. In the present study, the TBR did not diVer between the dentate and the edentulous subjects, although an age-related decrease in the TBR has been reported [23]. Age-related changes of mandible were well explained in previous studies.…”
Section: Discussionsupporting
confidence: 53%
“…The results of this study indicate that the TBR values of mandibular condyles are signiWcantly higher in dentate subjects than in edentulous subjects. One study of the TBR of the mandibular body found that the TBR diVered signiWcantly between dentate and edentulous groups in the molar region [23]. TBR was measured in this study to evaluate bone mineral density (BMD).…”
Section: Discussionmentioning
confidence: 99%
“…However, the present study indicated that the mandibular trabecular bone density does not differ by sex and is not altered with increasing age, which is consistent with previous mandibular findings using CT 16) . A previous cadaveric study involving micro-CT also showed that the trabecular bone ratio at the mandibular molars did not differ by sex and was not correlated with age in dentate subjects 17) . Considering the above, the trabecular bone density would be unlikely to exhibit sex-related differences or age-dependent changes in dentate mandibles.…”
Section: Discussionmentioning
confidence: 99%
“…It may have resulted because of the limited sample size. A previous study using CT described that the trabecular bone ratio had greater values at the molars in dentate mandibles than in edentulous mandibles 17) ; however, a comparison between the dentate and the edentulous sides was not performed in the same subjects. The edentulous conditions were not limited in the partial molar regions, and furthermore, some subjects probably lost teeth early in their lives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation